Metamizole-Associated Adverse Events: A Systematic Review and Meta-Analysis - Kötter, Thomas; da Costa, Bruno R.; Fässler, Margrit; Blozik, Eva; Linde, Klaus; Jüni, Peter; Reichenbach, Stephan; Scherer, Martin (PLOS ONE, 2015)
Background Metamizole is used to treat pain in many parts of the world. Information on the safety profile of metamizole is scarce; no conclusive summary of the literature exists. Objective To determine whether metamizole is clinically safe compared to placebo and other analgesics. Methods We searched CENTRAL, MEDLINE, EMBASE, CINAHL, and several clinical trial registries. We screened the reference lists of included trials and previous systematic reviews. We included randomized controlled trials that compared the effects of metamizole, administered to adults in any form and for any indication, to other analgesics or to placebo. Two authors extracted data regarding trial design and size, indications for pain medication, patient characteristics, treatment regimens, and methodological characteristics. Adverse events (AEs), serious adverse events (SAEs), and dropouts were assessed. We conducted separate meta-analyses for each metamizole comparator, using standard inverse-variance random effects meta-analysis to pool the estimates across trials, reported as risk ratios (RRs). We calculated the DerSimonian and Laird variance estimate T2 to measure heterogeneity between trials. The pre-specified primary end point was any AE during the trial period. Results Of the 696 potentially eligible trials, 79 trials including almost 4000 patients with short-term metamizole use of less than two weeks met our inclusion criteria. Fewer AEs were reported for metamizole compared to opioids, RR = 0.79 (confidence interval 0.79 to 0.96). We found no differences between metamizole and placebo, paracetamol and NSAIDs. Only a few SAEs were reported, with no difference between metamizole and other analgesics. No agranulocytosis or deaths were reported. Our results were limited by the mediocre overall quality of the reports. Conclusion For short-term use in the hospital setting, metamizole seems to be a safe choice when compared to other widely used analgesics. High-quality, adequately sized trials assessing the intermediate- and long-term safety of metamizole are needed.